The The Influence of the Internal Auditor’s Performance on the Effectiveness of the Internal Control System: Empirical Study at Islamic College in Medan - Siti Aisyah; Kamilah , K; Nurul Jannah (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to analyze the influence of the role of the internal auditor's performance on the effectiveness of the internal control system. This study uses primary data with a questionnaire as a research source. Respondents in this study were internal auditors who worked in six tertiary institutions in the Medan area, totaling 31 (thirty one) respondents. The questionnaires distributed to the six tertiary institutions were 34 (thirty four) questionnaires and the questionnaires collected were 31 (thirty three) questionnaires. The sampling method used in this study was convenience sampling, while the data analysis method was carried out using multiple linear regression methods supported by the SPSS version 22 program. The results of this study indicate that the independent variables have no effect on the effectiveness of the internal control system, while the role of the auditor has an effect significantly to the effectiveness of the internal control system.